In vivo antidiabetic and ex-vivo antioxidant activities of dichloromethane extract of Xerophyta spekei - Michael Musila Ndile; Wycliffe Arika Makori; Cromwell Mwiti Kibiti; Mathew Piero Ngugi (Clinical Phytoscience)
Abstract Background The medicinal plant Xerophyta spekei is used among Embu and Mbeere communities to manage diabetes mellitus. However, its efficacy has never been evaluated in vivo. The purpose of this study was to investigate its quantitative phytochemical and antidiabetic potential. Extraction was done using Dichloromethane (DCM). Quantitative phytochemical analysis was conducted using GC-MS. To evaluate antidiabetic activity, groups of mice which included normal control, diabetic control, positive control, and extract-administered groups (50, 100, 150, and 200 mg/kg body weight) were used. Alloxan monohydrate was used to induce diabetes. Blood glucose of the mice was determined hourly for the first six hours, and once after 12 and 24 h on the first day. Thereafter, the blood glucose in mice was determined once a week for three weeks. During the experimental period of three weeks, body weights were determined. After 21 days, lipid profiles, kidney and liver function tests as well as ex vivo antioxidant assays were carried out. Results The phytochemicals classes identified included flavonoids, phenolic compounds, phytosterols, terpenoids, fatty acids, tocopherols and alkaloids. Stigmasterol had the highest concentration (12.99 ± 2.56 mg/g). The extract decreased blood glucose dose-dependently, with 200 mg/kg bw dose resulting in the highest % mean change (40.10 ± 0.95). The extract gradually decreased blood glucose during 21 days of treatment. It attenuated loss of body weight and aberrant biochemical parameters including liver and renal function tests as well as lipid profiles in diabetic mice. Furthermore, it reduced levels of malondialdehyde and enhanced enzymatic antioxidant activities in diabetic mice. Conclusions The study confirms that DCM extract X. spekei contains phytochemicals with antioxidant and antidiabetic properties. The findings authenticate the folkloric use of X. spekei in managing diabetes mellitus. The medicinal plant also serves as a potential source for developing antidiabetic agents.